Pre- and Postoperative Rehabilitation of Craniopagus Conjoined Twins: A Case Report. (21st September 2021) - Sahu, Pradeep Kumar; Singh, Garima; Gupta, Deepak Kumar; Mahapatra, Ashok Kumar; Kale, Shashank Sharad
Abstract: Aims: Describe the pre-operative and post-operative stages of physical therapy examination, rehabilitation interventions and outcomes in craniopagus conjoined twins (CCT). Methods: 27-months old total vertical types III CCT were admitted for surgical treatment. A structured rehabilitation program (functional mobility, balance training, sensory stimulation, communication, orthotic management, and caregiver education) was delivered post-operatively at different stages of surgery. The total duration of post-separation rehabilitation was 15 months for Twin A and 23 months for Twin B. Results: Pre-operative WeeFIM was 67/126 for both the twins. Post-separation, Twin A improved to a state of complete independence in walking, step climbing, and hand function with a discharge WeeFIM score of 84/126. However, Twin B was completely dependent in bed mobility and transfer activities during discharge (WeeFIM-18/126). Minimal change in functional status was noted in Twin B (discharge FSS score-19/30). Both the twins were transferred to a regional hospital for long-term care. At 67 months of age, Twin B lost his life due to chest infection. Conclusions: Vestibular based therapies, balance, and postural control may be prioritized in the rehabilitation process of CCT. Greater communication and coordination among physical, occupational therapists and other rehabilitation professionals are recommended for successful outcome in these unique cases.